Ultrasonographic identification of nerve pathology in neuralgic amyotrophy: Enlargement, constriction, fascicular entwinement, and torsion. Issue 4 (21st August 2015) - Arányi, Zsuzsanna; Csillik, Anita; Dévay, Katalin; Rosero, Maja; Barsi, Péter; Böhm, Josef; Schelle, Thomas
ABSTRACT Introduction The aim of this study was to characterize the ultrasonographic findings on nerves in neuralgic amyotrophy. Methods Fourteen patients with neuralgic amyotrophy were examined using high‐resolution ultrasound. Results Four types of abnormalities were found: (1) focal or diffuse nerve/fascicle enlargement (57%); (2) incomplete nerve constriction (36%); (3) complete nerve constriction with torsion (50%; hourglass‐like appearance); and (4) fascicular entwinement (28%). Torsions were confirmed intraoperatively and were seen on the radial nerve in 85% of patients. A significant correlation was found between no spontaneous recovery of nerve function and constriction/torsion/fascicular entwinement (P = 0.007). Conclusion Ultrasonographic nerve pathology in neuralgic amyotrophy varies in order of severity from nerve enlargement to constriction to nerve torsion, with treatment ranging from conservative to surgical. We postulate that the constriction caused by inflammation is the precursor of torsion and that development of nerve torsion is facilitated by the rotational movements of limbs. Muscle Nerve 52: 503–511, 2015